Reorienting to Expectations of Change - Elizabeth Grigoriu (Adult Education Research Conference, 2006)
This paper explains implicit and explicit theoretical assumptions of change and an emerging reorientation to expectations of change by using activity and meaning making theory to uncover a more expanded, integrated understanding of our expectations of change. The purpose of this reorganization is to better navigate social interactions as practitioner theorists.
Keywords: Adult learning; human activity; change